A study of Thyroid Function test and Lipid Profile in Pregnancy - Mahantesh Patil1 , Arpitha M R2 , Dayananda R3 , Meera S4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Pregnancy is known to create profound changes in the body. It causes hormonal changes in the bodywhich may lead to changes in lipid profile. TSH levels are usually suppressed due to very high levelsof Human chorionic gonadotropin (hCG) during the first half of the pregnancy. Thyroid dysfunction mayresult in various changes in triglycerides, phospholipids, cholesterol and other lipoproteins. Dyslipidemia, aconsequence of thyroid dysfunction, generally increases the risk for cardiovascular disease.The study was conducted in the Department of Biochemistry, MMC&RI, Mysore. 100 women with asingleton pregnancy irrespective of parity and gravida were enrolled and cases like chronic hypertension,Diabetes mellitus, Renal Disorders and Thyroid Disorders, Obstetric and Foetal Complications (Hydropsfoetalis, congenital foetal anomalies) were excluded from the study. Blood was analysed for thyroid andlipid profile.Conclusion: T3, T4 and TSH levels are within normal range during pregnancy. There is a positive correlationbetween TSH levels and cholesterol. This suggest that regular TSH and cholesterol estimation is veryimportant during pregnancy to reduce the maternal and fetal complications.